Hypouricemic and nephroprotective effects of palmatine from Cortex Phellodendri Amurensis: A uric acid modulator targeting Keap1-Nrf2/NLRP3 axis. (30th January 2023) - Ai, Gaoxiang; Huang, Ronglei; Xie, Jianhui; Zhong, Linjiang; Wu, Xiaoyan; Qin, Zehui; Su, Ziren; Chen, Jiannan; Yang, Xiaobo; Dou, Yaoxing
Abstract: Ethnopharmacological relevance: Palmatine (Pal) is a major bioactive alkaloid originated from ancient Chinese herbal medicine Cortex Phellodendri Amurensis (CPA), which has long been applied to treat hyperuricemia (HUA)-related diseases. Pal possesses potent anti-inflammatory and anti-oxidant effects against metabolic diseases. However, its potential beneficial effect against PO (potassium oxonate)/HX (hypoxanthine)-induced HUA remains elusive. Aim of the study: This study aimed to investigate the potential pharmacological effect and mechanism of Pal on PO/HX-induced HUA in mice. Material and methods: A mouse model of HUA was established by co-administration of PO/HX once daily for 7 consecutive days. The HUA mice were orally given three doses (25, 50 and 100 mg/kg) of Pal daily for a week. Febuxostat (Feb, 5 mg/kg) was given as a positive control. At the scheduled termination of the experiment, the whole blood, liver and kidney were collected for subsequent analyses. The concentrations of uric acid (UA), creatinine (CRE) and blood urea nitrogen (BUN), and activities of adenosine deaminase (ADA) and xanthine oxidase (XOD) were evaluated. Histopathological alterations of the kidney were detected by H&E staining. The inflammatory and oxidative stress status was detected by assay kits. Additionally, key proteins involved in the urate transporter, Keap1-Nrf2 and TXNIP/NLRP3 signaling pathways were evaluated by immunohistochemistry and Western blotting. Finally, molecular docking was employed to probe the binding characteristics of Pal and target proteins Keap1, NLRP3, URAT1 and HO-1. Results: Administration of Pal substantially decreased the elevated kidney weight, lowered UA, CRE and BUN levels, and attenuated abnormal histopathological alterations. Meanwhile, treatment with Pal also dramatically lowered hepatic XOD and ADA activities. Besides, Pal treatment effectively mitigated the renal inflammatory and oxidative stress markers. Further mechanistic investigation indicated Pal distinctly downregulated the protein levels of GLUT9 and URAT1, while up-regulated the expression levels of OAT1 and ABCG2. Pal also restored Nrf2 activation, promoted subsequent expression of anti-oxidative enzymes, and downregulated the expressions of TXNIP, NLRP3, apoptosis-associated speck-like (ASC), caspase-1, IL-1β and IL-18. Molecular docking analysis also indicated Pal firmly bound with Keap1, NLRP3, URAT1 and HO-1. Conclusions: These findings indicated that Pal exhibited favorable anti-HUA effect via modulating the expressions of transporter-related proteins and suppressing XOD activity. Furthermore, Pal also alleviated HUA-induced kidney injury, which was at least partially related to restoring Keap1-Nrf2 pathway and inhibiting TXNIP/NLRP3 inflammasome. Our investigation was envisaged to provide experimental support for the traditional application of CPA and CPA-containing classical herbal formulas in the management of HUA-related diseases and might provide novel dimension to the clinical application of Pal. Graphical abstract: Image 1 Highlights: Pal inhibited oxidative stress and inflammatory response in HUA mice. Pal alleviated HUA-elicited kidney injury via restoring Keap1-Nrf2 pathway. Pal ameliorated HUA-elicited kidney injury via inhibiting TXNIP/NLRP3 pathway. Pal has the potential to be exploited as a promising candidate for HUA treatment.